IN FOND MEMORY OF PROFESSOR DR. SHAKILA YACOB, SCHOLAR, MENTOR, AND BUILDER OF MINDS, 1962-2025 - Aszlan Bin Selamat (SEJARAH: Journal of the Department of History, 2025)
IN FOND MEMORY OF PROFESSOR DR. SHAKILA YACOB, SCHOLAR, MENTOR, AND BUILDER OF MINDS, 1962-2025